(untitled) (The Pakistan Development Review, 2025)
In 1980, the World Bank began to promote Participatory Irrigation Management (PIM) reforms to overcome inequities in the distribution of irrigation water. This paper attempt to map the land and water productivity under the PIM and Non-PIM irrigation schemes in the Indus Basin Irrigation System (IBIS). This study integrates the remotely sensed datasets along with the traditional survey approach for data collection to holistically understand the performance of different irrigation governance regimes. We found that although the reform area in Sindh is performing better on many equity-related indices, a considerable inequity still persists between the head and tail reaches of the main canal. The variation in crop choices is the main reason for disproportionate economic return per unit of land and water and the role of farmer’s organisation to reduce the inequitable distribution of the water resource has limited success so far. However, it is seen that farmers’ role in improved irrigation management can be enhanced with better future legislation and devolution of more power and authority rather than only responsibility. We propose that the PIM theory of change, accompanied by mobilisation activities designed to generate hydro-solidarity and support the enactment of new social roles in contexts of social power asymmetries, could improve outcomes under PIM.